2017
DOI: 10.1155/2017/4803262
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in Inflammatory Bowel Disease: A Retrospective Study

Abstract: Aim To investigate the epidemiology and risk factors of Clostridium difficile infections (CDI) in patients with inflammatory bowel disease (IBD). Methods This is a retrospective study of patients diagnosed with IBD. 1006 charts were screened and 654 patients met the inclusion criteria. Patients were divided into 2 cohorts based on the presence of prior diagnosis of CDI. Statistical analysis with Pearson's chi-squared and two-sample t-test was performed. Results The incidence of CDI among IBD patients was 6.7%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
(31 reference statements)
2
17
1
3
Order By: Relevance
“…However, the existing data from other countries indicate a significantly lower incidence of CDI (2.8–11.1%) in adult UC patients compared to our findings [17, 32]. Recent studies from Europe, Canada, and the United States suggesting a rate of 20–27% community-acquired CDI in the general population [33]. Other recent studies have reported that in the majority of IBD patients, CDI was contracted outside of the hospital and 47.2% of patients acquired CDI from the community [34].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, the existing data from other countries indicate a significantly lower incidence of CDI (2.8–11.1%) in adult UC patients compared to our findings [17, 32]. Recent studies from Europe, Canada, and the United States suggesting a rate of 20–27% community-acquired CDI in the general population [33]. Other recent studies have reported that in the majority of IBD patients, CDI was contracted outside of the hospital and 47.2% of patients acquired CDI from the community [34].…”
Section: Discussioncontrasting
confidence: 69%
“…We found a significant relationship between the presence of CDI and steroid treatment, previous surgery, the severity of UC and anti-inflammatory treatment (Table 2). Previous studies have demonstrated that in UC patients, CDI is prevalent and colonic complicity, female, recent surgery, colectomy, younger age, and systemic steroid therapy was independently associated with CDI [8, 17, 23, 3335]. Fourteen percent of our patients showed one or two episodes of recurrences during the study period.…”
Section: Discussionmentioning
confidence: 52%
“…Their results showed that incidence of CDI among IBD patients was 6.7% with equal prevalence of CDI among CD and UC, concluding that IBD patients are more vulnerable to CDI at a younger age and that IBD patients with CDI would require biologic therapy with increased rates of extra-intestinal manifestations. [26] These results are in agreement with our results, where some patients with both IBD & CDI had extra-intestinal manifestations (arthritis, uveitis, episcleritis or erythema nodosum).…”
Section: Clostridia Difficilesupporting
confidence: 93%
“…It was reported that IBD patients with C. difficile infections (CDI), manifest severe clinical symptoms; including, abdominal pain, diarrhea, bloody stools, and leukocytosis . According to the reports, high prevalence of CDI in patients with IBD was revealed . Evidently, the toxins produced by this bacteria, inactivate the Rho family proteins which are involved in intracellular signaling pathways .…”
Section: Ibd and Clostridium Difficilementioning
confidence: 99%